2020
DOI: 10.3390/nu12102915
|View full text |Cite
|
Sign up to set email alerts
|

Protein Intake and Frailty: A Matter of Quantity, Quality, and Timing

Abstract: Frailty is a geriatric syndrome that refers to a state of reduced resiliency to stressful events that occurs in response to physiological and/or psychosocial detriments. Frailty is a predictor of poor prognosis, given that frail older adults are at higher risk of many adverse health-related events. Hence, the identification of potential strategies to prevent the development and progression of frailty is of extreme importance for avoiding its negative outcomes. An adequate protein consumption is advocated as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 146 publications
(205 reference statements)
4
59
2
5
Order By: Relevance
“…It has previously been shown that plant-derived proteins may represent an inadequate source of the essential amino acids lysine and leucine [47][48][49], with a reduced capability to stimulate muscle protein synthesis [50][51][52][53][54][55], thereby promoting animal-derived proteins as the primary source for maintenance of muscle mass and function in older adults. However, several studies examining effects of plant-derived proteins on protein synthesis were based on isolated and generally low digestible plant sources, such as soya and wheat [24,25,51,52,56]. Interestingly, it has been suggested that no deficits regarding essential amino acids such as lysine would be expected to occur with relative intakes of plant-derived proteins below 70% of total intake [57].…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that plant-derived proteins may represent an inadequate source of the essential amino acids lysine and leucine [47][48][49], with a reduced capability to stimulate muscle protein synthesis [50][51][52][53][54][55], thereby promoting animal-derived proteins as the primary source for maintenance of muscle mass and function in older adults. However, several studies examining effects of plant-derived proteins on protein synthesis were based on isolated and generally low digestible plant sources, such as soya and wheat [24,25,51,52,56]. Interestingly, it has been suggested that no deficits regarding essential amino acids such as lysine would be expected to occur with relative intakes of plant-derived proteins below 70% of total intake [57].…”
Section: Discussionmentioning
confidence: 99%
“…This nutritional aspect deserves concern, given that animal protein is expected to provide higher amounts of BCAA than vegetal protein. 42 - 44 BCAAs are directly and indirectly involved in numerous metabolic processes in the neural system. 45 - 49 However, much attention has been paid to their effects on GLU metabolism, given that it might serve as a possible mechanistic explanation for the association between protein intake and cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Negative results of a dietary intervention in an elderly population in terms of gut microbiota composition modification were reported by Mitchell et al [ 84 ]. Based on the recommendations of increasing protein intake in the elderly [ 95 ], 30 individuals aged 70 or older were allocated either to a group consuming the recommended dietary allowance (RDA) of protein or to a group consuming twice the RDA for 10 weeks. No differences in the microbiota composition or in the faecal volatile organic compounds were detected as a consequence of the intervention.…”
Section: Gut Microbiota Targeted Interventions In the Elderlymentioning
confidence: 99%